Multimodale Analyse von Interaktion im fremdsprachlichen Klassenzimmer. Multimodal analysis of interaction in a foreign language class. - Hoffmann, Sabine (Glottodidactica, 2016)
The article offers a contribution to the interaction research in the foreign language teaching and learning. It starts with an overview of various research approaches to the foreign language teaching and learning, from the 60s to the present days. A multimodal analysis of an excerpt of videorecorded classroom interaction is then provided. The analysis is focused on several aspects of classroom participation and teaching sequences. Some implications of the present research for teachers' training are finally provided.